Simple Thermodynamic Model of the Extension of Solid Solution of Cu-Mo Alloys Processed by Mechanical Alloying - Ordonez, S (2011)
The objective of this work is proposing a simple thermodynamic model to explain the increase in the solubility limit of the powders of the Cu-Mo systems or other binary systems processed by mechanical alloying. In the regular solution model, the effects of crystalline defects, such as; dislocations and grain boundary produced during milling were introduced. The model gives results that are consistent with the solubility limit extension reported in other works for the Cu-Cr, Cu-Nb and Cu-Fe systems processed by mechanical alloying. © 2011 Elsevier B.V. All rights reserved.